TINJAUAN DAYA TAHAN DAN KEKUATAN OTOT LENGAN ATLET WUSHU SANDA PEKANBARU DIMASA PANDEMI COVID-19 - Julia Sihombing, Sheryn Tiar; Wijayanti, Ni Putu Nita; Mandan, Ali (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The importance of VO2Max and arm muscle strength is seen during competitions. The physical activity of athletes is different from normal as there are many challenges during the COVID-19 pandemic. The aim of this research was to assess the endurance and muscle strength of the Pekanbaru wushu sanda athletes during the COVID-19 pandemic. This research is a quantitative descriptive research, data collection using a survey method using test and measurement methods. The instrument for measuring VO2Max is the 12-minute aerobic test. Arm muscle strength instrument, using the Push Up test. The population in the research was 41 individuals. The number of samples is 10 persons, using a targeted sampling technique. Based on the results of the survey and discussion, it was concluded that the Wushu Sanda Pekanbaru athletes endurance for male seniors was in the good category on average and for female seniors in the poor and fair categories. Also, Wushu Sanda Pekanbaru athletes arm muscle strength for senior men is in the average category and for senior women is in the good category.Key Words : Wushu sanda, endurance, arm muscle strength.